Prevalence and treatment outcome of pulmonary and extra pulmonary pediatric tuberculosis in southwestern Iran - Seyed Mohammad Alavi; Shokrollah Salmanzadeh; Pejman Bakhtiarinia; Ali Albagi; Fatemeh Hemmatnia; Leila Alavi (Babol University of Medical Sciences, 2015)
Background: Knowledge about childhood tuberculosis (TB) in Iran is limited. This study aimed to determine the proportion of tuberculosis in children living in Khuzestan in southwest of Iran and its treatment outcomes.  Methods: In this retrospective study, the child's medical records registered in national TB program (NTP) unit of Khuzestan Health Center (KHC) for TB treatment from 2005 to 2010 were studied. Data including demographic, clinical presentation, laboratory test results, and treatment outcomes were extracted from the files and were analyzed.  Results: Of total 4104 new TB cases registered in KHC, 203 (4.9%) were children. The mean age was 10.7±4.3 years, and 75.7% of them were females. More than 84% of TB children cases were 10 years or older, whereas, young children (< 5 years old) accounted for 5.6%. Of the total studied cases, 57.1% were pulmonary TB and 42.9% were extra pulmonary, 91.7% were successfully treated and 8.3% had poor treatment outcome. The main risk factors for poor treatment outcome were: age <5 years (OR: 0.17, 95% CI, 0.04-0.76), low body weight (OR: 0.08, 95% CI, 0.01-0.60), household contact with cases of TB treatment failure (OR: 0.13, 95% CI, 0.03-0.52), and exposure to cigarette smoke odor inside the home (OR: 0.17, 95% CI, 0.05-0.56).  Conclusion: The proportion of pediatric TB in the region was lower than expected. The treatment success rate was higher than the rate defined in NTP. Special attention should be given to children aged less than five years, low body weight, contact with TB treatment failure cases, and exposure to cigarette smoke.